Characteristics of Lymphoproliferative Disorders with More Than One Aberrant Cell Population as Detected by 10‐Color Flow Cytometry. Issue 2 (18th August 2016) - Mahdi, Talal; Rajab, Amr; Padmore, Ruth; Porwit, Anna
Abstract : Background: We have evaluated the frequency of lymphoproliferative disorders with more than one aberrant population of monotypic B‐cells detected during routine hematopathological diagnostics. Materials and Methods: 2600 samples peripheral (blood, bone marrow, fine‐needle aspirate, lymph node, and pleural fluid cell suspensions) were analyzed using a 10‐color B‐cell panel and a 10‐color T‐cell panel. A 10‐color plasma cell/lymphoplasmacytic panel was performed when appropriate. Results: 790/2600 samples (30%) showed at least one aberrant B‐cell population and 27(1%) showed an aberrant T‐cell population. 41/790 samples (5.1%) showed two aberrant B‐cell populations. Thirteen patients had two B‐cell populations with different surface immunoglobulin restriction (one kappa+ and one lambda+), most with B‐cell chronic lymphocytic leukemia‐related phenotype. Five cases showed two B‐cell populations with the same light chain restriction but distinctly different immunophenotypes. In 23 cases, two populations had the same light chain restriction and differed by expression of one or 2 markers, thus, a possibility of intraclonal differentiation could not be excluded. Cases with possible intraclonal differentiation had a significantly higher proportion of aberrant B‐cells than those with two coexisting aberrant B‐cell populations (49.9% vs. 27.7%, p = 0.008). In only one sample one population of clonal B‐cell and one clonal T‐cell population with large granular lymphocyte related phenotype were found. Conclusion: Using our panels 5.1% of cases with lymphoproliferative disorder‐associated aberrant findings show two aberrant (clonal) lymphoid and/or plasma cell populations. © 2016 International Clinical Cytometry Society